Chloroquine and Hydroxychloroquine: Potentially Inappropriate Medications for Older Adults? - Milton Gorzoni (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Potentially inappropriate medications (PIMs) for older adults cause more adverse effects than benefits. The 2019 American Geriatrics Society Beers Criteria (2019BC) considered five clinical situations as PIM use in older adults. Can drug analysis, according to these situations, assist in the act of making prescriptions for older people? Seeking a practical example for this question, we assessed drugs currently questioned as to their safe use among older people. OBJECTIVE: To check if chloroquine and hydroxychloroquine fit the PIM criteria for older adults and whether this analysis is clinically applicable. METHODS: We systematized the objective based on the five clinical situations defined as PIM use in older adults by the 2019BC. RESULTS: Chloroquine and hydroxychloroquine fulfill, respectively, four and five of these clinical situations. This evaluation allowed the likely definition of these drugs as PIMs for older adults in a simple way, based on a brief analysis of the available literature. CONCLUSION: Chloroquine and hydroxychloroquine may be considered PIMs for older adults. We expect that this analysis can be replicated with other drugs and reduce iatrogenesis in older people.